2020
DOI: 10.1186/s13148-020-00937-y
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose DNA demethylating therapy induces reprogramming of diverse cancer-related pathways at the single-cell level

Abstract: Background Epigenetic reprogramming using DNA demethylating drugs is a promising approach for cancer therapy, but its efficacy is highly dependent on the dosing regimen. Low-dose treatment for a prolonged period shows a remarkable therapeutic efficacy, despite its small demethylating effect. Here, we aimed to explore the mechanisms of how such low-dose treatment shows this remarkable efficacy by focusing on epigenetic reprograming at the single-cell level. Methods Expression profiles in HCT116 cells treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…First trials with DMTIs yielded promising treatment results, but they also evoked severe side effects 104,105 . Lower treatment dosages of DMTIs were similarly successful, but no major demethylation effect was observed in bulk sequencing experiments in contrast to higher treatment concentrations 106,107 . Analysis of monoclonal populations of the human colon carcinoma cell line HCT116 showed that every clone has a distinct partial demethylation pattern and that the resulting changes in epigenetic regulation are sufficient to slow cancer cell proliferation 107 .…”
Section: Epigenetic Analyses Of Cancer At Single‐cell Resolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…First trials with DMTIs yielded promising treatment results, but they also evoked severe side effects 104,105 . Lower treatment dosages of DMTIs were similarly successful, but no major demethylation effect was observed in bulk sequencing experiments in contrast to higher treatment concentrations 106,107 . Analysis of monoclonal populations of the human colon carcinoma cell line HCT116 showed that every clone has a distinct partial demethylation pattern and that the resulting changes in epigenetic regulation are sufficient to slow cancer cell proliferation 107 .…”
Section: Epigenetic Analyses Of Cancer At Single‐cell Resolutionmentioning
confidence: 99%
“…104,105 Lower treatment dosages of DMTIs were similarly successful, but no major demethylation effect was observed in bulk sequencing experiments in contrast to higher treatment concentrations. 106,107 Analysis of monoclonal populations of the human colon carcinoma cell line HCT116 showed that every clone has a distinct partial demethylation pattern and that the resulting changes in epigenetic regulation are sufficient to slow cancer cell proliferation. 107 This monoclonal analysis exemplified the necessity for single-cell resolution in cancer epigenetics in order to unravel cellular heterogeneity, to device novel therapies and to monitor treatment.…”
Section: Epigenetic Analyses Of Cancer At Single-cell Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demethylating agents are currently used to treat myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML). They are also being experimentally used in solid tumours in low dose administration, with very promising results [ 39 , 40 ]. Recent studies have shown an epigenetic involvement in several human fibrotic disorders [ 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that histone deacetylase inhibitor trichostatin A and CGK1026 induce IFI16 gene expression in prostate cancer cells ( 33 ). In addition, at a single-cell level, low dose treatment with DNA demethylating agents induces IFI16 gene expression ( 34 ). On the other hand, EGCG is a promoter demethylation-mediated epigenetic drug that induces expression of tumor suppressor genes in colon cancer cells ( 35 ).…”
Section: Introductionmentioning
confidence: 99%